Discourse of future-orientedness as neoliberal ideal: metaphor scenarios as a means of representing neoliberal logics - E., Marissa K. L. (Critical discourse studies, 2021)
Neoliberalism is a pervasive hegemonic phenomena that manifests in variegated ways which can be associated with the numerous trajectories that it undertakes as it pervades various geographical contexts. This paper examines the metaphorical representations of neoliberal logics in the Singapore higher education context with the aim of elucidating how neoliberalism is applied towards particular objectives that are deemed as necessary and relevant by the Singapore state. The paper focuses specifically on the discourse of future-orientedness as state-sanctioned neoliberal ideal and utilises conceptual metaphor theory, in particular metaphor scenarios, to show how the discourse of future-orientedness is represented under the associated theme of being ready to face/facing challenges. Corporate newsletters from two Singapore universities, NUS and SMU, with their varied institutional backgrounds, are utilised for the analysis. What emerges from the analysis is a representation of the ideal neoliberal subject as agent, with characteristics of preparedness, being well-equipped, and possession of the ability to embrace change and move forward into an unknown, possibly adverse future. This representation is then linked to the specific context of Singapore, with its particular contextual factors that have enabled the entrenchment of particular types of hegemonic neoliberal logics as neoliberal ideal valorised by the state.